A methods engineering on See Sew Collection - Cruz, Jay Ferdinand (College of Engineering, 1999)
The Philippines is specifically known for producing various garment products for well known foreign brand names like Levi's, GAP, Esprit, Osh Kosh B'gosh, and Guess. These locally manufactured products are produced for export purposes only. A lot of garment exporters and subcontractors are scattered throughout the country. They all share in meeting the demands of foreign enterprises. See Sew Collection is one of those subcontracted garment exporters and subcontractors are scattered throughout the country. They all share in meeting the demands of foreign enterprises. See Sew Collection is one of those subcontracted garments companies, which produces various products for export, such as baby wear, jogging pants, and T-shirts. The company started its operation in January 1995. The company's first operation was the manufacture of plain, white, roundneck shirts (aside from its own production, it also started to engage in subcontracting jobs to increase investment.) Initially it began its operation with only 12 machines. At present, the company manufactures products for export and has been subcontracting to different export companies. The company has also expanded its product line and now operates with 50 machines and 40 workers at hand. A documentation of the company's present system was done to identify specific problem areas. The main problem is the delay in production due to improper design of layout, lack of containers for bundles per operation, and absence of specific place for finished bundles after a process. The group recommends that the company invest in crates or boxes for the bundles and a shelf for the storage of stocks. Ideally, one box per worker should be bought since each worker works on a certain bundle. These bundles would be placed inside these boxes. The time wasted after every finished bundle would be minimized since this eliminates the time of tying the bundles for transport or storage. The group also recommends that the company should create a designated place for storing of the bundles. It is a divider type storage made of wood. Obstruction would be minimized and the workspace maximized. The proper storage of stocks could also be achieved. This would also complement the latter recommendation of providing crates. Changes in the layout like the rearrangement of machines or the movement of stocks and tables are also recommended in order to facilitate a better flow of materials and ease of control of production of multiple job orders. The group also recommends that the company should provide additional forms and to standardize its forms distribution.